2018
DOI: 10.3389/fmicb.2018.01759
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Insights Into Energy Metabolism of Carboxydocella thermautotrophica Coupling Hydrogenogenic CO Oxidation With the Reduction of Fe(III) Minerals

Abstract: The genus Carboxydocella forms a deeply branching family in the class Clostridia and is currently represented by three physiologically diverse species of thermophilic prokaryotes. The type strain of the type species, Carboxydocella thermautotrophica 41T, is an obligate chemolithoautotroph growing exclusively by hydrogenogenic CO oxidation. Another strain, isolated from a hot spring at Uzon caldera, Kamchatka in the course of this work, is capable of coupling carboxydotrophy and dissimilatory reduction of Fe(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 96 publications
0
25
0
Order By: Relevance
“…In Thermincola potens, MHCs are responsible for respiratory electron CooA-and c Rex-binding sequence motifs. The sequence logo is shown above each sequence alignment, and the number of bases from the start codon is shown in parentheses transfer to Fe(III) (Carlson et al 2012), and genomic analysis of Carboxydocella thermoautotrophica indicated the possible involvement of MHCs in CO-dependent Fe(III) reduction (Toshchakov et al 2018). Similar to these hydrogenogenic carboxydotrophs, C. maritimus KKC1 produces Fe(II) with ferric citrate, amorphous Fe(III) oxide, and Fe 2 O 3 in the presence of CO, suggesting that Fe(III) is used as an electron acceptor under CO conditions (Yoneda et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Thermincola potens, MHCs are responsible for respiratory electron CooA-and c Rex-binding sequence motifs. The sequence logo is shown above each sequence alignment, and the number of bases from the start codon is shown in parentheses transfer to Fe(III) (Carlson et al 2012), and genomic analysis of Carboxydocella thermoautotrophica indicated the possible involvement of MHCs in CO-dependent Fe(III) reduction (Toshchakov et al 2018). Similar to these hydrogenogenic carboxydotrophs, C. maritimus KKC1 produces Fe(II) with ferric citrate, amorphous Fe(III) oxide, and Fe 2 O 3 in the presence of CO, suggesting that Fe(III) is used as an electron acceptor under CO conditions (Yoneda et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These six cooS genes harbor the complete sequence motifs that form three types of metal clusters for catalysis, although cooS1 is frame-shifted like other hydrogenogenic, carboxydotrophic Moorella and Carboxydothermus species possibly as a result of cultivation at high CO concentrations (Wu et al 2005;Omae et al 2017;Poehlein et al 2018;Fukuyama et al 2018Fukuyama et al , 2019b. To the best of our knowledge, the genome contains the highest number of cooS genes (Omae et al 2017;Toshchakov et al 2018) and encodes six hydrogenase gene clusters that include two ech gene clusters, a cootype gene cluster (ech1, KKC1_RS06640-KKC1_RS06665) with cooS2, and a hyc/hyf-type gene cluster (ech2, KKC1_ RS01155-KKC1_RS01200) with putative formate dehydrogenase genes (Omae et al 2017). The genome only harbors one cooA gene as a CO-responsive transcription factor.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…This potential is lower than that of the H + /H 2 redox couple, meaning that CO can replace H 2 as an electron donor for microorganisms carrying genes encoding for carbon monoxide dehydrogenase (CODH). The CODH gene cluster in the genus, Carboxydocella, consists of 13 genes encoding for: redox-and CO-sensitive transcriptional regulator (cooA), [Ni, Fe]-CODH (cooS), [Ni, Fe]-CODH accessory nickel-insertion protein (cooC), CO-induced hydrogenase membrane anchor (cooM), energy-converging hydrogenase (cooKLXUH), hydrogenase maturation protein (hypA), 4Fe-4S di-cluster domain containing electron transfer protein (cooF), energy-converging hydrogenase catalytic subunit (cooH), and the upstream enigmatic cooSC operon of unknown function (Toshchakov et al, 2018). The upstream cooS gene is notably missing in the closely related Carboxydothermus hydrogenoformans (Toshchakov et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This potential is lower 57 than that of the H + /H2 redox couple, meaning that CO can replace H2 as an electron 58 donor for microorganisms carrying genes encoding for carbon monoxide 59 dehydrogenase (CODH). The CODH gene cluster in the genus, Carboxydocella, 60 consists of 13 genes encoding for: redox-and CO-sensitive transcriptional regulator 61 (cooA), [Ni, Fe]-CODH (cooS), [Ni, Fe]-CODH accessory nickel-insertion protein 62 (cooC), CO-induced hydrogenase membrane anchor (cooM), energy-converging 63 hydrogenase (cooKLXUH), hydrogenase maturation protein (hypA), 4Fe-4S di-cluster 64 domain containing electron transfer protein (cooF), energy-converging hydrogenase 65 catalytic subunit (cooH), and the upstream enigmatic cooSC operon of unknown 66 function (Toshchakov et al, 2018). The upstream cooS gene is notably missing in the 67 closely related Carboxydothermus hydrogenoformans (Toshchakov et al, 2018).…”
Section: Introduction 48mentioning
confidence: 99%
“…The CODH gene cluster in the genus, Carboxydocella, 60 consists of 13 genes encoding for: redox-and CO-sensitive transcriptional regulator 61 (cooA), [Ni, Fe]-CODH (cooS), [Ni, Fe]-CODH accessory nickel-insertion protein 62 (cooC), CO-induced hydrogenase membrane anchor (cooM), energy-converging 63 hydrogenase (cooKLXUH), hydrogenase maturation protein (hypA), 4Fe-4S di-cluster 64 domain containing electron transfer protein (cooF), energy-converging hydrogenase 65 catalytic subunit (cooH), and the upstream enigmatic cooSC operon of unknown 66 function (Toshchakov et al, 2018). The upstream cooS gene is notably missing in the 67 closely related Carboxydothermus hydrogenoformans (Toshchakov et al, 2018). The 68 catalytic subunit of CODH is composed of the CooS protein, while the CooF electron-69 transfer protein is known to associate with redox reactions such as the production of H2 70 or reduced metals (Soboh et al, 2002).…”
Section: Introduction 48mentioning
confidence: 99%